Supernumerary teeth: Report of four unusual cases - Arun Kumar; Ritu Namdev; Lokesh Bakshi; Samir Dutta (Wolters Kluwer Medknow Publications, 2012)
Supernumerary tooth denotes duplication of tooth in the normal series. It is a developmental anomaly and has been argued to arise from multiple etiologies. These teeth may remain embedded in the alveolar bone or can erupt into the oral cavity. The supernumerary tooth might cause esthetic and/or functional problems, especially if it is situated in the maxillary anterior region. Complications reported were delayed or prevented eruption of succedaneous teeth, displacement or rotation, crowding of the affected region, abnormal diastema, dilacerations, cystic formation, and sometime eruption into the nasal cavity. In this case report, four unusual cases of supernumerary teeth that resulted in varying degrees of disturbances in permanent dentition are presented. Conservative surgical intervention and light orthodontic forces were used to bring the teeth into normal position with minimal disturbance to the surrounding oral structures.